Sustained replication of dengue pseudoinfectious virus lacking the capsid gene by trans-complementation in capsid-producing mosquito cells - Sangiambut S. (2014)
A simple system for the generation of pseudoinfectious particles of dengue virus was developed to facilitate studies of virus replication and vaccine development. Selected clones of the C6/36 mosquito cell line expressing an anchored form of the dengue virus capsid protein served as host cells for the trans-complementation of partially capsid-deleted viral RNA generated in vitro. Transfection of the partially capsid-deleted viral RNA into the anchored capsid-expressing C6/36 cells resulted in moderate titers of infectious virus. Progeny viruses multiplied in the capsid trans-complementing C6/36 cells for up to three weeks, but only initiated single rounds of replication in Vero cells lacking the capsid protein. Employing this trans-complementation system, it was found that nearly all of the capsid-coding sequence in the viral RNA was dispensable for the generation of pseudoinfectious dengue virus particles in mosquito cells. © 2013 Elsevier B.V.